Research on Level of Management Information Systems Use by the Construction Companies in Bulgaria - Bobchev, Konstantin (Research Papers, 2022)
The object of the research is the construction branch in Bulgaria, the subject is the significance of specialized software use in companies’ activities in the situation of pandemic. The study is provoked by the necessity to organize the business activities in a crisis circumstances and it puts accent on determining level of multifunctional information systems use. The reasons for the low level of this use is commented, as well as the tasks in front of the construction companies in order the maximum benefits of ERP systems to be obtained optimizing the daily business processes, decreasing expenses, increasing incomes, improving the quality of the final products and services the construction companies offer.